2021
DOI: 10.1208/s12249-021-02106-7
|View full text |Cite
|
Sign up to set email alerts
|

Salts and Polymorph Screens for Bedaquiline

Abstract: Bedaquiline is used to treat multi-resistant tuberculosis in adults. The fumarate salt is commercially available and used in the product Sirturo. To provide open access to bedaquiline molecule once the patent on the chemical substance expires, new salts were screened. This work offers additional information on the bedaquiline system, as new salts may present better pharmacokinetic properties. The current studies focus on the attempted isolation of the acetate, benzoate, benzenesulfonate, hydrobromide, succinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…This caused economic damage of more than 250 million dollars. , Therefore, it is strategic to take control of pharmaceutical solid-state forms by using different and effective crystallization process regulations. The preparation methods of the solid-state forms can be classified as thermal and solution methods, including melting method, sublimation method, evaporation method, cooling method, reaction method, antisolvent method, and other novel methods, which indicate the complication of preparing different crystal forms, hence informing us the necessity for solid-state form screening. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This caused economic damage of more than 250 million dollars. , Therefore, it is strategic to take control of pharmaceutical solid-state forms by using different and effective crystallization process regulations. The preparation methods of the solid-state forms can be classified as thermal and solution methods, including melting method, sublimation method, evaporation method, cooling method, reaction method, antisolvent method, and other novel methods, which indicate the complication of preparing different crystal forms, hence informing us the necessity for solid-state form screening. , …”
Section: Introductionmentioning
confidence: 99%
“…The preparation methods of the solid-state forms can be classified as thermal and solution methods, including melting method, 20−22 sublimation method, 23 evaporation method, 24 cooling method, 25 reaction method, 26 antisolvent method, 27 and other novel methods, 28 which indicate the complication of preparing different crystal forms, hence informing us the necessity for solid-state form screening. 29,30 The external conditions of the solution crystallization processes, such as the cooling method, antisolvent method, and slurry method, are decisive for obtaining solid-state forms. Song et al 31 reported the pyrazinamide polymorphism in different solvent systems, whereas Fondren et al 32 reported how the external conditions such as various temperatures or crystallization solvents affected the polymorphism development in 2,4,6-trinitrotoluene.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that no new polymorph was formed at the 10 kg laboratory scale for the benzoate salt. The full details of the polymorph screening results for bedaquiline benzoate were published in an earlier communication [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the salicylate salt was not characterized further. On the other hand, the benzoate salt had the highest probability for success because it was possible to synthesize it using several routes, which have been extensively discussed in two earlier publications [ 3 , 15 ] The malonate and nicotinate salts were successfully synthesized via the slow evaporation of a 1:1 mixture of acetone and 2-propanol.…”
Section: Discussionmentioning
confidence: 99%
“…New salts of BDQ have been developed and characterized. 2 4 These salts will encourage additional organizations to manufacture BDQ. BDQ benzoate and maleate have been identified as promising salts.…”
mentioning
confidence: 99%